ANALISIS PENGARUH PENUNTASAN LIMA PILAR PROGRAM SANITASI TOTAL BERBASIS MASYARAKAT (STBM) TERHADAP PENURUNAN PENYAKIT DIARE DI KECAMATAN BRANG ENE KABUPATEN SUMBAWA BARAT - SAHARUDDIN SAHARUDDIN; UMAR UMAR; RODIANTO RODIANTO (Universitas Mahasaraswati K. Mataram, 2024)
The aim of the research is to determine the mechanism for completing the Five Pillars of the Community-Based Total Sanitation Program (STBM) on reducing Diarrhea and to determine the influence of the Five Pillar Factors on the success of the Community-Based Total Sanitation Program (STBM) on reducing Diarrhea. in Kalimantong Village, Brang Ene District, West Sumbawa Regency. This research method uses mixed methods research with qualitative and quantitative approaches, the location or place of this research was carried out in Kalimantong Village, Brang Ene District, West Sumbawa Regency. The data collection techniques used were questionnaires, interviews, observations, informants, events, documentation, while to obtain For more accurate data, data analysis is used, namely carrying out Validity and Reliability Tests, Classical Assumption Tests, Multiple Linear Regression Tests and Hypothesis Testing. The results of the research are that the mechanism for completing the Five Pillars of the Community-Based Total Sanitation Program (STBM) in Kalimantong Village has been carried out until it reaches 100% completion, so that the implementation of the Five Pillars of the Community-Based Total Sanitation Program (STBM) is concluded to have an effect on reducing diarrheal disease in Kalimantong Village, Brang District. Ene, West Sumbawa Regency. The results of the Hypothesis Test analysis can be concluded that the variable Stop Open Defecation (Stop BABS) has a tcount of 4.291 and the variable Washing Hands with Soap (CTPS) has a tcount of 5.396, which has an effect on reducing diarrheal disease in Kalimantong Village, Brang Ene District. Meanwhile, the Household Drinking Water and Healthy Food Management (PAMRT) variable has a tcount of -1.685, the Household Waste Management (PSRT) variable has a tcount of -4.590, the Household Wastewater Management (PALRT) variable has a tcount of -3.236 with no significant effect. on the reduction of diarrheal diseases in Brang Ene District, West Sumbawa Regency.